Integrating WHO’s digital adaptation kit for antenatal care into BornFyne-PNMS: insights from Cameroon - Nkangu, Miriam; Tangang, Brice; Pessa, Arthur; Weledji, Donald; Obegu, Pamela; Kasonde, Mwenya; Ngo, Ngo V.; Wanda, Franck; Gobina, Ronald M.; Kibu, Odette; Shiroya, Veronica; Foretia, Denis; et al. (Frontiers in pharmacology, 2025)
BackgroundDigital health innovations represent unique opportunities to address maternal, newborn, and child health challenges in Sub-Saharan Africa. In 2021, the World Health Organization (WHO) launched the Digital Adaptation Kits (DAKs) for antenatal care (ANC) as part of its Standards-Based, Machine-Readable, Adaptive, Requirements-Based, and Testable (SMART) guidelines approach. DAKs are operational and software-neutral mechanisms that convert WHO guidelines into standardized formats that can be easily integrated into digital systems by various countries. This article outlines the methodology for updating and integrating WHO DAK content into the BornFyne-prenatal management system (PNMS) version 2.0.MethodsThis study, which employs a participatory action research approach, is part of a larger research study for the BornFyne-PNMS project. A review of the ANC DAK operational document and data dictionaries was conducted to identify elements that were present in BornFyne-PNMS version 1.0. This was followed by a series of consultations and stakeholder meetings.ResultsFive stakeholder meetings were held to engage stakeholders across Cameroon. Some of the registration elements, among other DAK aspects of ANC service provision, were identified in BornFyne version 1.0 but required reorganizing, remodeling, and reanalyzing to align with the International Classification of Diseases codes and DAK data content as part of the expansion for BornFyne version 2.0. Up to 40% of the DAK dictionary data content existed within the BornFyne-PNMS version 1.0, including additional DAK content adapted to update BornFyne-PNMS version 2.0. The digital health ecosystem in Cameroon is in an emerging phase with an increasing demand for digital health technologies, especially in the areas of reproductive, maternal, newborn, child, and adolescent health.ConclusionThe digital health ecosystem in Cameroon is in an emerging phase with an increasing demand for digital health technologies, especially in the area of reproductive, maternal, newborn, child, and adolescent health. This article describes and documents the steps in operationalization of the ANC DAK content into the BornFyne-PNMS content, highlighting the DAK as an important tool for guiding and facilitating software engineers in developing and integrating recommended ANC guidelines into digital platforms to facilitate interoperability, going by the structure of the document, its workflow processes, and content mapping elements.